The relationship between right ventricular outflow tract fractional shortening and Pulmonary Embolism Severity Index in acute pulmonary embolism - Ekrem Şahan; Murat Karamanlıoğlu; Suzan Şahan; Murat Gül; Ahmet Korkmaz; Omaç Tüfekçioğlu (KARE Publishing, 2017)
Objective: Right ventricular (RV) functions are clinically important in acute pulmonary embolism (APE). Measurement of systolic function of the right ventricular outflow tract (RVOT) with echocardiography is a simple method to evaluate RV function. The aim of this study was to determine the relationship between RVOT systolic function and the Pulmonary Embolism Severity Index (PESI). Methods: A total of 151 patients diagnosed with APE by pulmonary computed tomography angiography or ventilation/perfusion scintigraphy were included. Patients were assigned to 2 groups based on the simplified PESI (sPESI): sPESI <1 (n=85) and sPESI ≥1 (n=66). RV conventional parameters, RVOT dimensions, and fractional shortening (RVOT-FS) were also measured. Results: Mean age was similar between sPESI <1 and >1 patients (58.7+-12.9 years vs. 61.1+-12.7 years, respectively). Frequency of male gender was significantly higher in PESI <1 group (61.2% vs. 40.2%, p=0.013). No significant differences were found between the groups in fasting glucose, serum creatinine, hemoglobin, C-reactive protein, erythrocyte sedimentation rate, troponin, and D-dimer levels, and left ventricular ejection fraction. RVOT-FS was higher in patients with sPESI <1 than in patients with sPESI ≥1 (34.41+-3.56 vs. 22.98+-4.22), and this difference was significant (p<0.001). Tricuspid annular plane systolic excursion values were lower and pulmonary artery systolic pressure values were higher in the sPESI ≥1 group, which was also statistically significant (p<0.05). Mortality occurred in 7 patients with sPESI <1 and in 16 patients with sPESI ≥1. The mortality rate was higher in patients with lower RVOT-FS, and a RVOT-FS <0.22 predicted mortality with a sensitivity of 54.5% (AUC: 0.674, 95% CI 0.552-0.796; p=0.009). Conclusion: The RVOT-FS is a noninvasive measurement of RV systolic function, is well-correlated with the sPESI score, and associated with mortality in patients with APE. This easily applied measurement may be used to predict short-term mortality in patients with APE.